Do the quantitative relationships of synaptic junctions and terminals in the thalamus of genetic absence epilepsy rats from Strasbourg (GAERS) differ from those in normal control Wistar rats - ONAT, FİLİZ (SPRINGER-VERLAG ITALIA SRL, 2012)
Abnormal functional properties of the thalamocortical connections were reported in the absence of epilepsy. The present study compares the ratios of terminals (`RL'-round vesicles, large terminals, 'RS'-round vesicles, small terminals and 'F'-flattened vesicles) and synapse in three first-order (ventrobasal, lateral geniculate and anteroventral) and in three higher-order (posterior, lateral posterior and mediodorsal) thalamic nuclei of genetic absence epilepsy rats from Strasbourg (GAERS) with our earlier quantitative studies of normal Wistar rats to show whether quantitative differences were present in GAERS as compared to Wistar rat. Rats were perfused transcardially, the brains were removed and cut as 300 lmcoronal sections. Parts of the six thalamic nuclei were removed for routine electron microscopy and GABA immunocytochemistry. Twenty photographs from each section at 20,0009 magnification were taken, and the terminals were identified as RL, RS or F. (1) In normal Wistar rats (as in cats), the proportion of driver terminals (RL) and synapses is lower in higherorder than in first-order thalamic nuclei, but this difference is not present in GAERS animals. (2) The proportions of RS terminals and synapses for each thalamic nucleus showed no significant differences between GAERS and Wistar rats for any of the thalamic nuclei. (3) In GAERS, the proportion of inhibitory F terminals and synapses was significantly high in the VB and low in the LP thalamic nucleus. These abnormal ratios in the GAERS may be the cause of the spike-and-wave discharges of absence seizures or may represent a compensatory response of the thalamocortical circuitry to the absence seizures.
Keywords: Electron microscopy; Immunohistochemistry; Thalamus; GABA; Drivers; Modulators; LATERAL GENICULATE-NUCLEUS; RETICULAR NUCLEUS; HIGHER-ORDER; WAVE DISCHARGES; PHA-L; CORTICOTHALAMIC PROJECTIONS; GABAERGIC TRANSMISSION; SOMATOSENSORY THALAMUS; RELATIVE DISTRIBUTION; ANTEROGRADE TRACER